Effect of tropical grass and nitrogen fertilization on nitrous oxide, methane, and ammonia emissions of maize-based rotation systems. (1st August 2020) - Grassmann, Camila S.; Mariano, Eduardo; Rocha, Kassiano F.; Gilli, Bruno R.; Rosolem, Ciro A.
Abstract: While tropical grasses were shown to inhibit the activity of soil nitrifiers, their role in greenhouse gas (GHG) and ammonia (NH3 ) emissions in N fertilized maize-based rotations are poorly understood. A 3-year (2014–2017) field experiment was conducted in southeastern Brazil to assess the influence of forage grass and N fertilization on nitrous oxide (N2 O), methane (CH4 ), and NH3 emissions from maize ( Zea mays L.)-grass rotations. Guinea grass ( Megathyrsus maximus cv. Tanzânia), palisade grass ( Urochloa brizantha cv. Marandu), and ruzigrass ( Urochloa ruziziensis cv. Comum) were grown in the main plots, while an unfertilized control and 140 kg N ha −1 were applied annually to maize in sub-plots. No apparent nitrification suppression by the grasses was detected. N2 O fluxes increased following N fertilizer addition in maize, particularly in the second season, where slightly higher cumulative N2 O emission was observed with N fertilization in comparison with the control. CH4 fluxes showed high variation in the first forage and maize growing seasons. Residual N fertilizer decreased soil CH4 uptake of palisade grass and ruzigrass compared with unfertilized palisade grass in the second forage season. Cumulative NH3 emissions were unaffected by forage species and N fertilization. However, in both maize seasons, yield-scaled NH3 emission was the lowest following N addition. Throughout the seasons, the differences between the three grasses in N2 O, CH4, and NH3 emissions were minimal. We conclude that the tropical perennial grasses rotated with maize were similar regarding GHG and NH3 emissions, while N fertilization slightly increased N2 O emission and decreased soil CH4 uptake. Highlights: We measured GHG and NH3 emissions in N-fertilized rotations over three years. There is no clear evidence of nitrification suppression by the forage grasses. Tropical forage grasses are similar regarding N2 O, CH4, and NH3 emissions. Nitrogen fertilization slightly increases N2 O emission and decreases soil CH4 uptake. Yield-scaled NH3 emission is higher in the control relative to N-fertilized soil.